The analysis of the disturbances in a morphological structure and a hormonal function of thyroid gland in women in perimenopausal period - Orlicz-Szczęsna, Grażyna; Wojciechowska, Katarzyna; Szczęsny, Piotr; Drozd-Styk, Ewa (Current Problems of Psychiatry, 2011)
It has been found out that there is a similarity between the symptoms of hyperthyroidism and perimenopausal period. The similarity between the symptoms of ovarian function suppression and excessive thyrocytes activity significantly prolongs the time of making proper diagnosis in women in perimenopausal period. The aim of this study was to evaluate the relation between the morphological structure of thyroid gland and the frequency of hyperthyroidism during the perimenopausal period. The comparison of thyroid hormonal disturbances was made in two groups of women in perimenopausal period: those suffering from nodular goiter and those with immunological Graves-Basedow disease. The analysis of the group of 146 women in age 46-54 in perimenopausal period was made. All of the patients have visited endocrinologist for 10 years. Our studies points to a high percentage of activation of thyroid gland during the perimenopausal period. The women with the neutral nodular goiter are particularly predisposed to hyperthyroidism during the perimenopausal period.Graves-Basedow disease in the past with a long period of remission was a rare reason of the resume of hyperthyroidism in a menopausal period. The most frequent morphological changes, which caused the hyperthyroidism, were hot nodules and warm nodules-single and coexisting with cold nodules. In ten years time of observation, the morphological changes in scintigraphy were observed. The most frequent form of changes was the development of hot and warm nodules on the basis of warm, cold and cool areas.The patients during perimenopausal period should be very well diagnosed because of the similarity of the symptoms in hyperthyroidism and menopausal period.